Differentiation of Multi-lithotypes Olistostromal Occurrences Associated with Iron Enrichment and Mineralization Within the Ophiolites of Choman Area, NE Iraq - Barzan K. Azo; Kamal Kolo; Mohammad Pirouei (Tikrit Journal of Pure Science, 2023)
The discovery of multi-lithotypes olistostromes deposits associated with potentially economically viable iron ore mineralizations in the Rayat region of NE Iraq are described in this study. The depositional and differentiation-classification characteristics of multi-lithotypes of olistostromes with distinct depositional and characteristics are reported here through detailed petrographic, mineralogical, and geochemical data, that allowed for mineralization mechanisms assessment and associated hydrothermal and alteration processes. Ferruginous conglomerate lithotypes occur below the sandstone olistostromes lithotypes section of the investigated series. Through the ferruginous conglomerate olistostromes (FCO) lithotypes there is a layer of potentially iron ore containing iron oxide (up to %42.55), quartz with some minor spinel content. Below the FCO, there are the horizons of (FOpO and FSO), they are also rich in hematite quartz and calcite with some minor spinel content. A 2m thick transition zone (TZ), separate poorly mineralized ophiocarbonatic olistostrome (OpCO) from the FCO. The multi-lithotypes of olistostrome from bottom to top are (serpentinite olistostrome (SO), Ophiocarbonatic olistostrome (OpCO), ferruginous serpentinite olistostrome (FSO), ferruginous ophiocarbonatic olistostrome (FOpCO), ferruginous conglomerate olistostrome (FCO), and sandstone olistostrome (SstO). In addition to Fe, the other potential economic importance element includes nickel (507 to 5816 mg/kg) and cobalt (47.2 to 328.3 mg/kg). The findings indicate that the Rayat olistostromes such as (SO, FSO, OpCO, FOpCO, FCO, and SstO) and the transition- zone (TZ) originated from a mixture of early hydrothermal alteration of serpentinites. The finding of olistostromes in the Rayat, exposes NE Iraq as a potential mineral-rich secto